2022
DOI: 10.3390/ijms23147637
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Deletion of Bmal1 Impairs Placental Vascularization and Induces Intrauterine Fetal Death in Mice

Abstract: Recently, it was demonstrated that the expression of BMAL1 was decreased in the endometrium of women suffering from recurrent spontaneous abortion. To investigate the pathological roles of uterine clock genes during pregnancy, we produced conditional deletion of uterine Bmal1 (cKO) mice and found that cKO mice could receive embryo implantation but not sustain pregnancy. Gene ontology analysis of microarray suggested that uterine NK (uNK) cell function was suppressed in cKO mice. Histological examination reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Recently, we generated mice with a conditional deletion (cKO) of uterine Bmal1 to examine the pathogenic functions of the uterine clock genes during pregnancy [ 75 ]. We found that cKO mice could achieve embryo implantation but could not maintain pregnancy.…”
Section: Effects Of the Circadian Clock On The Hypothalamic–pituitary...mentioning
confidence: 99%
“…Recently, we generated mice with a conditional deletion (cKO) of uterine Bmal1 to examine the pathogenic functions of the uterine clock genes during pregnancy [ 75 ]. We found that cKO mice could achieve embryo implantation but could not maintain pregnancy.…”
Section: Effects Of the Circadian Clock On The Hypothalamic–pituitary...mentioning
confidence: 99%
“…Based on this background, to investigate the pathological roles of uterine clock genes during pregnancy, we produced conditional deletion of uterine Bmal1 (cKO) mice [16] using Bmal1-loxP [38] and progesterone receptor-cre mice as reported previously [39,40]. As a result, cKO mice could receive embryo implantation, but not sustain the pregnancy.…”
Section: Uterine Deletion Of Bmal1 Induces Intrauterine Fetal Death I...mentioning
confidence: 99%
“…Furthermore, Daikoku et al created mice deficient in the uterus-specific clock gene Bmal1 and observed that the fetuses died before delivery, indicating that abnormal uterine clock function cannot maintain fetal development. The cause of this phenomenon was elucidated to be abnormal placentation accompanied by a failure in the construction of maternal blood vessels, indicating the possibility that reproductive and perinatal diseases are induced by abnormal uterine clock [16].…”
Section: Introductionmentioning
confidence: 99%
“…As the core circadian locomotor output cycle kaput (CLOCK) gene, BMAL1 is rhythmically expressed in many tissues, including uterine and placental tissues, and is responsible for controlling the circadian expression of numerous target genes involved in many physiological processes [11,12]. It has been suggested that reduced endometrial BMAL1 expression is associated with an increased risk of spontaneous recurrent miscarriages in humans [13,14]. Decidual cells deficient in BMAL1 expression showed inhibitory effects on trophoblast invasion into uterine spiral arteries [15].…”
mentioning
confidence: 99%
“…These findings at the molecular level should prompt a reassessment of the systemic consequences of disruption of the biological clock, especially with regard to fertility [16]. Moreover, the insufficient invasion of trophoblast cells, which is the main factor involved in the development of pre-eclampsia, is caused by the impaired activity of natural killer (NK) cells [14,15]. Therefore, if the cytolytic activity in NK cells required for trophoblast invasion follows a daily rhythm, it may be disrupted as a result of decreased BMAL1 expression [17].…”
mentioning
confidence: 99%